Relationship Between Family Participation in Sport/Recreational Activities and Marital and Life Satisfaction - Narges Memar Bahabadi; Bagher Morsel; Seyed Mostafa Tayebisani; Ali Fahiminezhad (Gonabad University of Medical Sciences, 2020)
Background: This study aimed to investigate the relationship between family participation in sport/recreational activities and marital satisfaction and life satisfaction. Methods: The study was survey-correlational research. The statistical population included all families living in Mashhad City. Using the cluster sampling method, six parks were selected from the different regions of Mashhad. Then, the researcher referred to the selected parks and distributed the questionnaires to families who came together for recreation in the park. Considering the unknown number of populations, the statistical sample was determined as 384 individuals, based on the Morgan table. To reach the sample size, 500 questionnaires were distributed, however, 430 questionnaires were returned. Data collection tools included the Handrich marital satisfaction questionnaire and the Newgarten life satisfaction questionnaire. Using the Cronbach alpha coefficient, the reliability was calculated as 0.82 for the marital satisfaction questionnaire and as 0.88 for the life satisfaction questionnaire. Also, we used descriptive statistics, the Kolmogorov-Smirnov test, the Cronbach alpha, the Pearson correlation test, and linear regression for data analysis, in SPSS V. 22. Results: The findings showed that 54.18% of the respondents were female. Besides, most of the participants (75.8%) were in the age range of 30 to 60 years. The results of the hypotheses testing showed a significant relationship between marital satisfaction and the weekly, monthly, and annual participation of families in sport/recreational activities. Also, life satisfaction was significantly associated with the weekly, monthly, and annual participation of families in sport/recreational activities. Conclusion: Totally, 19.99% of the total variance of life satisfaction is predicted by marital satisfaction